Process Evaluation of a Pilot Physical Activity and Social-Emotional Learning Curriculum Implemented in a Summer Care Program for Child and Adolescent Girls - Tyler Prochnow; Deja T. Jackson; Laurel S. Curran; Jeong-Hui Park; Meg Patterson; Robert F. Valois (Health Behavior Research)
Physical activity (PA) and social-emotional learning (SEL) are critical for healthy development, yet few programs have evaluated integrated promotion efforts within out-of-school summer contexts. The EmpowerHER program was piloted in a summer care program for girls. This study aimed to conduct a process evaluation, assessing the program's fidelity to curriculum design and theory to make recommendations for continuous program improvement. The EmpowerHER curriculum was tailored towards girls (n=11, 10-14 years old) and implemented through a community summer care program. The 8-week program consisted of 90-minute sessions conducted twice per week during the summer of 2023 in Texas, USA. Fidelity was evaluated using the System for Observing Fitness Instruction Time (SOFIT), which characterized participant PA levels, lesson context, social interactions, and instructor interactions. Participants wore ActiGraph GT9X accelerometers to measure PA and completed surveys to assess perceptions of activities. SOFIT observations revealed varying levels of PA across sessions, with peaks in Sessions 4 (26%) and 5 (12%). Accelerometer data showed higher light PA (M=18.3±6.1 min) compared to moderate-to-vigorous PA (M=9.6±4.9 min) per session. Surveys indicated high enjoyment (M=4.6±0.3), learning (M=4.1±0.1), and perceived PA engagement (M=4.5±0.2). Participants expressed preferences for interactive activities and more gym time. Triangulating multi-method process data enabled nuanced optimization of intervention components session-by-session. The curriculum balanced educational components with PA opportunities, but would benefit from more consistent PA. Positive social interactions and participant feedback highlighted the program's potential to enhance SEL. Future iterations should prioritize activities that foster positive relationships and maximize PA.